The Additive Effect of Low Molecular Weight Heparins on Thrombin Inhibition by Dermatan Sulfate - Cosmi, Benilde; Agnelli, Giancarlo; Young, Edward; Hirsh, Jack; Weitz, Jeffrey (Thrombosis and Haemostasis, 1993)
The aim of this study was to investigate the mechanism by which the anticoagulant activity of dermatan sulfate (DS) is increased by low molecular weight heparin (LMWH). In platelet poor plasma, LMWH enhances the effect of DS on thrombin (IIa) inhibition as determined by thrombin clotting times and with a chromogenic substrate assay. Analysis of the results of the chromogenic assays using either the algebraic fractional or the graphic isobole method suggests that LMWH has an additive effect on the anti-IIa activity of DS. This additive effect was lost when the experiments were repeated in plasma immunodepleted of antithrombin III (ATIII), indicating that the anti-IIa activity of LMWH is ATIII-dependent. To further explore the mechanism of the interaction between LMWH and DS, 125I-labeled IIa was added to plasma in the presence or absence of DS and/or LMWH and the formation of IIa-inhibitor complexes was assessed using SDS-PAGE followed by autoradiography. DS addition selectively increases the formation of heparin cofactor II (HCII)-IIa complexes, whereas LMWH enhances ATIII-IIa complex generation. Compared to plasma containing DS alone, the formation of ATIII-IIa complexes also is increased when the combination of DS and LMWH is added. These findings suggest that the additive effect of LMWH on the anti-IIa activity of DS reflects their different modes of IIa inhibition; DS potentiates IIa inhibition by HCII, while LMWH catalyses ATIII-dependent IIa inactivation. The potential clinical significance of these findings requires further investigation.